An exploration of gendered violence in engineering spaces experienced by women in Latin America - Merchán-Rubiano, Sandra Milena; Rodríguez-Simmonds, Héctor E.; Sánchez-Peña, Matilde; García De Cajén, Silvia; Acero, Andrés; Pascal, Guadalupe (LACCEI, 2025)
This full paper presents preliminary results from a broader research project analyzing the stories of successful Latin American women in engineering published as part of the CAL Matilda. Framed under the consideration of direct, systemic and cultural violence, we explore what expressions of gendered violence are found in the lived narratives of successful women engineers in Latin America through a qualitative inductive process. Our preliminary results showcase experiences with public discrimination, the need to prove their capabilities, dealing with gender exclusive spaces, facing jokes and insults related to gender, as well as the experience of sexual harassment. We present how this work will continue, and how its results could support the advancement of our understanding of gendered violence in engineering spaces.